2019
DOI: 10.24297/jam.v17i0.8419
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric Approach for Solving Interval–Valued fractional Continuous Static Games

Abstract: The aim of this paper is to show that a parametric approach can be used to solve fractional continuous static games with interval-valued in the objective function and in the constraints. In this game, cooperation among all the players is possible, and each player helps the others up to the point of disadvantage to himself, so we use the Pareto-minimal solution concept to solve this type of game. The Dinkelbach method is used to transform fractional continuous static games into non- fractional continuous static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Khalifa and Kumar [21] investigated cooperative continuous static games in a crisp environment, defining and determining the first-kind stability set corresponding to the solution without differentiability. Under uncertainty environment, some recent researchers for cooperative games have been introduced (Mallozzi and Messalli [22], Bigdeli and Hassanpour [23], Elshafei [24], Zaichenko [25], Zidan et al [26], Donahue et al [27], Ganzfried [28], Zhou et al [29], Krishankumar et al [30,31], Tukhtasinov et al [32], Sivagami et al [33], Zhao et al [34], Megahed [35], Romanuke [36], and Khalifa et al [37]).…”
Section: Introductionmentioning
confidence: 99%
“…Khalifa and Kumar [21] investigated cooperative continuous static games in a crisp environment, defining and determining the first-kind stability set corresponding to the solution without differentiability. Under uncertainty environment, some recent researchers for cooperative games have been introduced (Mallozzi and Messalli [22], Bigdeli and Hassanpour [23], Elshafei [24], Zaichenko [25], Zidan et al [26], Donahue et al [27], Ganzfried [28], Zhou et al [29], Krishankumar et al [30,31], Tukhtasinov et al [32], Sivagami et al [33], Zhao et al [34], Megahed [35], Romanuke [36], and Khalifa et al [37]).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the information available to each player consists of the cost functions and constraints. Elshafei [8] familiarized an interactive model for solving Nash CSG and resulted a stability set accordingly. Hosseinzadeh Lotfi et al [9] applied Nash bargaining theory, for performance assessment, and suggested a model of data envelopment analysis.…”
Section: Introductionmentioning
confidence: 99%